1998
DOI: 10.1002/(sici)1096-9071(199809)56:1<85::aid-jmv14>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Estimated susceptibility to asymptomatic secondary immune response against measles in late convalescent and vaccinated persons

Abstract: Serological evidence indicates that measles virus (MV) could circulate in seropositive, fully protected populations. Among individuals fully protected against disease, those prone to asymptomatic secondary immune response are the most likely to support subclinical MV transmission. The serological characteristics of protected subjects who developed secondary immune response after reexposure to measles have been described recently [Huiss et al. (1997): Clinical and Experimental Immunology 109:416-420]. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…However, considerable evidence suggests that this may not be the case given that asymptomatic measles virus infection has been well documented in vaccinated children. 27 Recently, it was demonstrated that macaques vaccinated with live attenuated virus or DNA can experience subclinical infection when challenged with measles virus. 28 Studies have shown that the therapeutic efficacy of conditionally replicating adenoviruses, 29 herpesviruses, 30 or reoviruses 4 was not negated by pre-existing antiviral antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, considerable evidence suggests that this may not be the case given that asymptomatic measles virus infection has been well documented in vaccinated children. 27 Recently, it was demonstrated that macaques vaccinated with live attenuated virus or DNA can experience subclinical infection when challenged with measles virus. 28 Studies have shown that the therapeutic efficacy of conditionally replicating adenoviruses, 29 herpesviruses, 30 or reoviruses 4 was not negated by pre-existing antiviral antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that this may not be the case, since examination of the immune response of convalescent children suggested that MV infection can occur after vaccination without resulting in disease (15). Moreover, it was recently shown that macaques vaccinated with live attenuated virus or DNA can experience a subclinical infection at challenge (40).…”
Section: Discussionmentioning
confidence: 99%
“…We know, for example, that the sera of convalescent measles patients or of those who have been vaccinated variably neutralize the wild virus strains [4] but, conversely, the neutralizing capacity of the polyclonal response of B-cells, whether induced by infection or by vaccination, is not affected or influenced by the genotype [5]. So did this strain have an increased virulence, giving it a selective advantage, e.g.…”
mentioning
confidence: 99%